Temperature and loading sensitivity investigation of nanoindentation short-term creep behavior in Nafion®. (1st February 2019) - Zhang, Zhennan; Tian, Chenyao; Yuan, Ziqi; Li, Jiejie; Wu, Wen-Ping; Xia, Re
Abstract: Contemporary energy challenges have triggered a growing interest in the fuel cell membrane technology in recent years, embracing Nafion ® membranes. Creep-induced failure caused by temperature and load is an important lifetime limiting failure mode in fuel cell applications. In this study, experiments were conducted to measure the creep behaviors in Nafion ® (115, 117, 211, 212) membranes in thickness direction on the basis of nanoindentation method. It was carried out for a range of temperatures (40–80 °C) and applied peak loads (24–56 μ N) respectively. Findley's and Burger's models were used to analyze the results and it illustrates the instantaneous elastic deformation, retarded elastic deformation and retardation time increase significantly as the test temperature or peak load rises. A substantial increase of creep displacement is found over 70 °C due to glass transition. The mechanism of polymer creep is interpreted with an emphasis on microstructure molecular. Based on a defined dimensionless parameter, load effect on creep is higher than that of temperature effect.